Preparation method of sulfonated biochar material PC-SO3H-1 and application of sulfonated biochar material PC-SO3H-1 in field of biomass conversion
By loading sulfonic acid groups on biochar to form sulfonated biochar PC-SO3H-1 catalytic material, the existing photothermal catalytic technology is solved, and efficient photothermal conversion and biodiesel are achieved high yields.
Patent Information
- Application Number
- CN202411670564.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-07
AI Technical Summary
The existing photothermal catalysis technology faces problems such as unsustainable, inefficient photothermal conversion and high cost, and is difficult to be widely used in the production of biodiesel.
Using sulfonated biochar PC-SO3H-1 catalytic material, the sulfonic acid group was successfully supported onto the carbon material by combining cellulose with hydrothermal method to form an efficient photothermal catalyst.
It achieves efficient photothermal conversion, significantly improves the yield of biodiesel, reduces preparation costs, and is easy to recycle, which is in line with the concept of green chemistry.
Smart Images

Figure HDA0005145734800000011 
Figure HDA0005145734800000012 
Figure HDA0005145734800000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photothermal catalysis technology and biomass resource utilization technology, and specifically relates to a sulfonated biochar PC-SO3H-1 catalytic material and a preparation method and application thereof. Background Art
[0002] In human activities, the extensive use of non-renewable fossil fuels has caused a series of major issues of global concern, such as environmental pollution, energy depletion and greenhouse effect. In order to further solve these problems and meet the challenges brought by climate change, the promotion of renewable energy has become a top priority. Among them, biodiesel, as a high-quality substitute for fossil diesel, has low toxicity and biodegradability. It can not only mix well with traditional fossil diesel, but also reduce greenhouse gas emissions. Generally, biodiesel can be converted through the transesterification reaction of triglycerides and short-chain alcohols or the esterification reaction of free fatty acids and short-chain alcohols under catalysis.
[0003] Generally speaking, traditional thermal catalytic technology is simple to operate, but it mainly relies on additional heating with electric energy, which easily causes huge energy consumption. Environmentally friendly photocatalytic technology, although it can convert solar energy into chemical energy under mild reaction conditions, is often severely restricted by the limited separation and migration efficiency of photocarriers, resulting in a significant reduction in catalytic efficiency, which seriously hinders the widespread application of this technology. Therefore, photothermal catalytic technology, which can convert solar energy into thermal energy and chemical energy, has attracted great attention due to its environmental protection, unprecedented light capture efficiency, and no need for additional energy supply. Photothermal catalytic technology not only makes up for the limitations of photocatalysis and thermal catalysis, significantly improves the selectivity and efficiency of the reaction, but also effectively reduces the activation energy of the reaction. Photothermal catalytic technology can increase the reaction rate to an industrial level and become a promising solution for large-scale production of fuels using solar energy. However, the currently widely used photothermal materials, such as precious metals and semiconductors, still face a series of challenges such as unsustainability, low photothermal conversion efficiency, and high cost. Therefore, it is particularly important to develop a new type of photothermal material that is efficient, low-cost and environmentally friendly. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for preparing a sulfonated biochar PC-SO3H-1 catalytic material, comprising the following steps:
[0005] (1) pretreating, washing, drying and grinding cellulose to obtain pretreated cellulose powder;
[0006] (2) Pre-treated cellulose powder, p-toluenesulfonic acid and citric acid are made into a mixed aqueous solution, and then the mixed aqueous solution is transferred to a high-pressure reactor for reaction, and then cooled, washed, dried, and ground to obtain the PC-SO3H-1 photothermal catalytic material.
[0007] Furthermore, the pretreatment conditions in step (1) are: ultrasonically treating cellulose with a 5-15 wt% NaOH aqueous solution for 0.5-1 h, washing until the filtrate is neutral, and drying at a temperature of 60-80°C.
[0008] Furthermore, the mixed aqueous solution in step (2) is prepared by uniformly dispersing the pretreated cellulose powder, p-toluenesulfonic acid and citric acid in deionized water and stirring for 30 minutes.
[0009] Furthermore, in the mixed aqueous solution in step (2), the mass ratio of the pretreated cellulose powder, p-toluenesulfonic acid and citric acid is 1:(0-2):(0-2).
[0010] Furthermore, the reaction conditions in step (2) are: temperature 140-180° C., reaction time 8-14 h.
[0011] Furthermore, the conditions in step (2) are: drying temperature 60-80° C., and drying time 12-48 hours.
[0012] The present invention also provides a sulfonated biochar PC-SO3H-1 catalytic material, which is prepared by the above preparation method.
[0013] The present invention also provides application of the PC-SO3H-1 catalytic material in producing biodiesel.
[0014] The present invention has the following beneficial effects:
[0015] 1. The photothermal catalytic material of the present invention has a simple and easy preparation method, is green and environmentally friendly, and is easy to recycle. Its raw material is renewable natural polymer cellulose, which is abundant in source and low in cost, and can greatly reduce the preparation cost, which is in line with the concept of green chemistry.
[0016] 2. The sulfonated biochar photothermal catalyst of the present invention has strong absorption in the visible light and near-infrared light regions, can effectively utilize solar energy, obtain a higher photothermal conversion efficiency, and make up for the deficiencies of photocatalysis and thermal catalysis.
[0017] 3. The present invention adopts photothermal catalytic biodiesel production technology with mild reaction conditions, and can prepare biodiesel at room temperature and normal pressure, thus avoiding the energy consumption problem caused by traditional thermal catalytic technology under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 XRD diagrams of different samples in the present invention;
[0020] Figure 2 FT-IR spectra of different samples in the present invention;
[0021] Figure 3 It is the nitrogen adsorption-desorption and pore size distribution diagram of different samples in the present invention;
[0022] Figure 4 are SEM images of different catalysts prepared in the present invention, wherein A is a SEM image of cellulose, B is a SEM image of pretreated fiber, C is a SEM image of pretreated cellulose hydrothermal carbon, D is a SEM image of PC-1, E is a TEM image of PC-SO3H, and F is a SEM image of PC-SO3H-1;
[0023] Figure 5 This is a graph showing the change in yield over time of oleic acid produced by photothermal catalysis of PC-1 material for biodiesel under the conditions of an alcohol-oil molar ratio of 20:1 and a catalyst dosage of 4wt%.
[0024] Figure 6 This is a graph showing the change in yield over time of oleic acid produced by photothermal catalysis of PC-SO3H material under the conditions of an alcohol-oil molar ratio of 20:1 and a catalyst dosage of 4wt%.
[0025] Figure 7 This is a graph showing the change in yield over time of oleic acid produced by photothermal catalysis of PC-SO3H-1 material for biodiesel under the conditions of an alcohol-oil molar ratio of 20:1 and a catalyst dosage of 4wt%. DETAILED DESCRIPTION
[0026] Now, various exemplary embodiments of the present invention are described in detail. The methods in the examples are conventional methods unless otherwise specified, and the reagents used are conventional commercially available reagents or reagents prepared by conventional methods unless otherwise specified. This detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, features and embodiments of the present invention.
[0027] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] The embodiment of the present invention provides a method for preparing a sulfonated biochar PC-SO3H-1 catalytic material, comprising the following steps:
[0032] (1) The cellulose is ultrasonically pretreated with an aqueous NaOH solution, washed, dried, and ground to obtain a pretreated cellulose powder.
[0033] (2) The pretreated cellulose powder, p-toluenesulfonic acid and citric acid are uniformly dispersed in deionized water and fully stirred at room temperature, and then the solution is transferred to a high-pressure reactor for reaction, cooling, washing, drying, and grinding to obtain the PC-SO3H-1 photothermal catalytic material.
[0034] In some specific embodiments, in step (1), the pretreatment conditions are: ultrasonically treating cellulose with 5-15 wt% NaOH aqueous solution for 0.5-1 h, washing until the filtrate is neutral, and drying at 60-80°C.
[0035] In some specific embodiments, in step (2), the mixed solution is prepared by uniformly dispersing the pretreated cellulose powder, p-toluenesulfonic acid and citric acid in deionized water and stirring for 30 minutes.
[0036] In some specific embodiments, in step (2), it is characterized in that the preparation method of the mixed solution is: the mass ratio of the pretreated cellulose powder, p-toluenesulfonic acid and citric acid is 1: (0-2): (0-2).
[0037] In some specific embodiments, in step (2), it is characterized in that the temperature of the hydrothermal process is 140-180° C., and the reaction time is 8-14 hours; the drying temperature is 60-80° C., and the drying time is 12-48 hours.
[0038] The embodiment of the present invention provides the PC-SO3H-1 catalytic material obtained by the preparation method.
[0039] Among many catalytic materials, carbon materials are favored because of their highly adjustable structure, chemical inertness, low cost and earth abundance. At the same time, they can also efficiently absorb the entire spectrum, making them an ideal photothermal material. In addition, the present invention combines the carbonization and sulfonation processes into one step through a simple hydrothermal method, successfully achieving the loading of sulfonic acid groups on carbon materials, and greatly enriching the active sites. The sulfonated biochar of the present invention not only exhibits excellent photothermal conversion capabilities and can quickly induce high temperature effects, but its abundant active sites can also effectively enrich the reaction substrates and promote the chemical equilibrium to move in the positive direction, thereby significantly improving the photothermal catalytic performance. Therefore, the sulfonated biochar PC-SO3H-1 material of the present invention can be used as a low-energy, high-efficiency photothermal catalyst and applied to the actual production of biodiesel.
[0040] The embodiment of the present invention provides the application of the PC-SO3H-1 photothermal catalytic material in the production of biodiesel.
[0041] The embodiment of the present invention provides a method for producing biodiesel, which utilizes the PC-SO3H-1 material for photothermal catalysis to produce biodiesel using substrate oil as raw material.
[0042] In some specific embodiments, the base oil includes at least one of oleic acid, palmitic acid, stearic acid, palm oil, Koelreuteria hupehensis oil, Xanthium sibiricum oil, Datura seed oil, Sterculia truncatula seed oil, Jatropha curcas oil or castor oil.
[0043] In some specific embodiments, the PC-SO3H-1 photothermal catalytic material accounts for 3-7 wt % of the substrate oil.
[0044] Example 1
[0045] 1. Preparation of sulfonated biochar PC-SO3H-1 photothermal catalyst
[0046] 4 g of cellulose was added to 80 mL of NaOH aqueous solution (15 wt%) and ultrasonically treated for 30 min. After the ultrasonic treatment, the cellulose was repeatedly washed with deionized water until the filtrate became neutral, dried at 80° C. for 12 h, and ground to obtain pretreated fiber powder.
[0047] 2g of pretreated cellulose powder, 2g of citric acid and 2g of p-toluenesulfonic acid were added to 20mL of deionized water and stirred for 30min to mix thoroughly. The solution was then transferred to an autoclave and kept at 180°C for 10h, washed with deionized water and anhydrous ethanol until the filtrate was neutral, and dried at 80°C overnight. The PC-SO3H-1 photothermal catalytic material was obtained by grinding.
[0048] 2. Catalytic activity test
[0049] 1 g of oleic acid, 2.82 mL of methanol and 0.04 g of photocatalyst were added to a quartz photoreactor, a 300 W xenon lamp was used as the light source, and the resulting mixture was stirred at room temperature for 30 min. After the reaction was completed, the upper liquid phase was extracted with petroleum ether, and the residual methanol and petroleum ether were removed by a rotary evaporator to obtain purified biodiesel. 1 The corresponding biodiesel yield was determined by H NMR and calculated to be 98.29%.
[0050] Example 2
[0051] 1. Preparation of Biochar PC-1 Photothermal Catalyst
[0052] The preparation conditions of the catalyst were exactly the same as those in Example 1, except that the mass of p-toluenesulfonic acid added in the preparation method was changed to 0 g, and the hydrothermal carbon PC-1 catalyst was obtained under the condition that the mass ratio of cellulose to citric acid was 1:1.
[0053] 2. Catalytic activity test
[0054] The reaction conditions were the same as in Example 1, but the reaction time was changed to 3 h, and the yield of biodiesel was 9.45%.
[0055] Example 3
[0056] 1. Preparation of sulfonated biochar PC-SO3H photothermal catalyst
[0057] When the preparation conditions of the catalyst are exactly the same as those in Example 1, except that the mass of citric acid in the preparation method is changed to 0 g, and the mass ratio of cellulose to p-toluenesulfonic acid is 1:1, the sulfonated biochar PC-SO3H photothermal catalyst is obtained.
[0058] 2. Catalytic activity test
[0059] The reaction conditions were the same as those in Example 1, and the yield of biodiesel was 71.68%.
[0060] Example 4
[0061] 1. Preparation of sulfonated biochar PC-SO3H-1 catalyst
[0062] Same as Example 1.
[0063] 2. Catalytic activity test
[0064] The reaction conditions were the same as those in Example 1, except that the oleic acid was replaced by stearic acid, and the yield of biodiesel was 97.64%. When the oleic acid was replaced by jatropha oil or palm oil, the yields of biodiesel were 90.42% and 92.11%, respectively, after the reaction was carried out for 4 hours.
[0065] Characterization results:
[0066] PC is pretreated cellulose; PCC is the biochar obtained by direct hydrothermal treatment of pretreated cellulose; PC-1 is the biochar obtained by hydrothermal treatment of PC with only citric acid; PC-SO3H is the sulfonated biochar obtained by hydrothermal treatment of PC with only p-toluenesulfonic acid; PC-SO3H-1 is the sulfonated biochar obtained by hydrothermal treatment of PC with the synergistic participation of p-toluenesulfonic acid and citric acid.
[0067] The XRD patterns of different samples in the present invention are as follows: Figure 1 As shown, the curve of cellulose shows a typical type I cellulose crystal structure peak. After pretreatment with NaOH aqueous solution, the type I cellulose crystal peak disappeared, and the curve of PC showed a new characteristic peak belonging to the type II cellulose crystal structure. The characteristic peak of PCC is similar to that of PC, but the peak intensity is significantly weaker. However, the three types of biochar prepared by acid-participated hydrothermal method all showed a broad C (002) diffraction peak in the range of 10° to 30°, which is a characteristic of amorphous carbon composed of aromatic carbon sheets arranged in a random manner.
[0068] The FT-IR spectra of different samples in the present invention are as follows: Figure 2 As shown in the figure, cellulose, PC and PCC have similar characteristic peaks, among which 1020cm -1 The strong peak of PC-1 belongs to the COC vibration of the pyran ring skeleton of cellulose. -1 The characteristic peaks appeared at 1170-561 cm -1 The new peaks appearing at belong to the -OH, COS and SO bond stretching vibrations of the sulfonic acid groups, indicating that the sulfonic acid groups were successfully grafted onto the carbon material.
[0069] Figure 3 These are the nitrogen adsorption - desorption and pore size distribution maps of different samples in the present invention. The isotherm of the biochar material shows a type - IV isotherm pattern with an H4 hysteresis loop, indicating the presence of micropores, mesopores, and narrow slit pores.
[0070] Figure 4 These are the electron micrographs of different materials prepared in the present invention. As Figure 4 shown in A, the surface structure of cellulose is dense, containing fine broken fibers. After pretreatment, the surface becomes an irregular and loose layered structure, with micropores emerging ( Figure 4 B). What is obtained after pure hydrothermal treatment is only fiber fragments with a smaller scale. However, under the catalytic action of acid, PC is transformed into hydrothermal carbonized spheres. This is because the water - insoluble fragments generated by cellulose during hydrothermal treatment become spherical to minimize environmental exposure. The diagrams of the PC - 1 or PC - SO3H materials obtained by separate hydrothermal treatment with citric acid or p - toluenesulfonic acid show the formation of carbon microspheres with a smaller diameter. However, the simultaneous participation of citric acid and p - toluenesulfonic acid leads to an increase in the diameter of the carbon spheres, which may be related to the excessive acidic environment.
[0071] Figure 5 This is a graph showing the change in the yield of photothermal - catalytic biodiesel with time for the PC - 1 material. At an alcohol - oil molar ratio of 20:1, a catalyst dosage of 4 wt%, room temperature, and light conditions, even after a reaction lasting 3 h, the yield of photothermal - catalytic biodiesel by the PC - 1 material cannot reach 10%.
[0072] Figure 6 This is a graph showing the change in the yield of photothermal - catalytic biodiesel with time for the PC - SO3H material. At an alcohol - oil molar ratio of 20:1, a catalyst dosage of 4 wt%, room temperature, and light conditions, the yield of photothermal - catalytic biodiesel by the PC - SO3H material can reach 71.68% within 30 min, indicating that the successful loading of the sulfonic acid group improves the photothermal - catalytic activity of the biochar.
[0073] Figure 7 This is a graph showing the change in the yield of photothermal - catalytic biodiesel with time for the PC - SO3H - 1 material. Under the same conditions, the yield of photothermal - catalytic biodiesel by the PC - SO3H - 1 material can reach 98.29% within only 30 min, which is far greater than that of PC - SO3H and PC - 1, indicating that the synergistic catalytic hydrothermal treatment of p - toluenesulfonic acid and citric acid on pretreated cellulose enables this material to obtain ideal photothermal - catalytic activity. And from the graph, it can be seen that the photothermal - catalytic activities of the three materials from low to high are in the order of: PC - 1 photothermal - catalytic material < PC - SO3H photothermal - catalytic material < PC - SO3H - 1 photothermal - catalytic material.
[0074] In summary, the present invention has wide applicability and low energy consumption, and the catalytic process does not require additional heating. It only relies on light and photothermal catalysts to quickly induce high temperatures, thereby directly converting substrates such as oleic acid into biodiesel. The photothermal catalyst has a wide spectral response range, excellent photothermal conversion efficiency and abundant active sites, and after 5 cycles of use, the biodiesel yield remains above 80%. In addition, the material preparation method is simple and easy, the reaction conditions are mild, the cost is low, and it is easy to recycle. It can be used as a new type of high-efficiency photothermal catalytic material with full spectrum response.
[0075] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing sulfonated biochar PC-SO3H-1 catalytic material, characterized in that: The following steps are involved: (1) pretreating, washing, drying and grinding cellulose to obtain pretreated cellulose powder; (2) Pre-treated cellulose powder, p-toluenesulfonic acid and citric acid are made into a mixed aqueous solution, and then the mixed aqueous solution is subsequently transferred to a high-pressure reactor for reaction, and then cooled, washed, dried, and ground to obtain the PC-SO3H-1 photothermal catalytic material.
2. The preparation method according to claim 1, characterized in that: The pretreatment conditions in step (1) are: ultrasonically treating cellulose with a 5-15 wt% NaOH aqueous solution for 0.5-1 h, washing until the filtrate is neutral, and drying at a temperature of 60-80°C.
3. The preparation method according to claim 1, characterized in that: The preparation method of the mixed aqueous solution in step (2) is: pretreated cellulose powder, p-toluenesulfonic acid and citric acid are uniformly dispersed in deionized water and stirred for 30 minutes.
4. The preparation method according to claim 1, characterized in that: In the mixed aqueous solution in step (2), the mass ratio of pretreated cellulose powder, p-toluenesulfonic acid and citric acid is 1:(0-2):(0-2).
5. The preparation method according to claim 1, characterized in that: The reaction conditions in step (2) are: temperature 140-180° C., reaction time 8-14 h.
6. The preparation method according to claim 1, characterized in that: The conditions in step (2) are: drying temperature 60-80° C., and drying time 12-48 hours.
7. A sulfonated biochar PC-SO3H-1 catalytic material, characterized in that: Prepared by any one of the preparation methods of claims 1 to 6.
8. Use of the PC-SO3H-1 catalytic material as claimed in claim 7 in the production of biodiesel.
Citation Information
Cited By
Preparation method of biomass derived sewage treatment agent
CN121927571A